Poly(ethylene glycol)-crosslinked gelatin hydrogel substrates with conjugated bioactive peptides influence endothelial cell behavior. (May 2019) - Su, Jimmy; Satchell, Simon C.; Wertheim, Jason A.; Shah, Ramille N.
Abstract: The basement membrane is a specialized extracellular matrix substrate responsible for support and maintenance of epithelial and endothelial structures. Engineered basement membrane-like hydrogel systems have the potential to advance understanding of cell-cell and cell-matrix interactions by allowing precise tuning of the substrate or matrix biochemical and biophysical properties. In this investigation, we developed tunable hydrogel substrates with conjugated bioactive peptides to modulate cell binding and growth factor signaling by endothelial cells. Hydrogels were formed by employing a poly(ethylene glycol) crosslinker to covalently crosslink gelatin polymers and simultaneously conjugate laminin-derived YIGSR peptides or vascular endothelial growth factor (VEGF)-mimetic QK peptides to the gelatin. Rheological characterization revealed rapid formation of hydrogels with similar stiffnesses across tested formulations, and swelling analysis demonstrated dependency on peptide and crosslinker concentrations in hydrogels. Levels of phosphorylated VEGF Receptor 2 in cells cultured on hydrogel substrates revealed that while human umbilical vein endothelial cells (HUVECs) responded to both soluble and conjugated forms of the QK peptide, conditionally-immortalized human glomerular endothelial cells (GEnCs) only responded to the conjugated presentation of the peptide. Furthermore, whereas HUVECs exhibited greatest upregulation in gene expression when cultured on YIGSR- and QK-conjugated hydrogel substrates after 5 days, GEnCs exhibited greatest upregulation when cultured on Matrigel control substrates at the same time point. These results indicate that conjugation of bioactive peptides to these hydrogel substrates significantly influenced endothelial cell behavior in cultures but with differential responses between HUVECs and GEnCs. Graphical abstract: Image 1